No evidence, no problem? A critical interpretive synthesis of the vulnerabilities to and experiences of sexual violence among young migrants in Europe - Tanya Andersson Nystedt; Tobias Herder; Anette Agardh; Benedict Oppong Asamoah (Taylor & Francis Group, 2024)
Background Growing evidence indicates that young migrants are particularly vulnerable to sexual violence, however most research has focused on instances of sexual violence occurring in conflict zones and during transit. Much less attention has been given to the vulnerabilities to and experiences of sexual violence among young migrants in Europe. Objectives To understand the scientific evidence regarding the experiences of and vulnerabilities to sexual violence among young migrants (aged 11-30 years) in Europe. Methods A search of three databases resulted in 1279 peer reviewed articles published between 2002 and 2022. Of these, 11 were included in this review. A critical interpretive synthesis methodology was applied. Results Few studies investigate sexual violence among young migrants in Europe. The existing studies focus on very specific sub-groups of migrants, and as such, experiences of persons outside these groups are largely absent from the academic discourse. How sexual violence is understood varies across studies, often conflated with other forms of violence, hampering comparisons. However, the results of this review indicate that young migrants in Europe, both male and female, experience sexual violence and there are multiple sources of vulnerabilities at all levels of the socioecological model. Conclusion The scarcity of research regarding sexual violence among young migrants in Europe could give rise to the perception that no evidence means no problem, resulting in a continued lack of attention to this issue. There is a critical need to address this gap to inform prevention interventions, to identify victims, and to facilitate access to care.